2023
DOI: 10.5551/jat.63557
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff Values of Brachial-Ankle Pulse Wave Velocity for Atherosclerotic Risks by Age and Sex in the Japanese General Population

Abstract: Results: As per our findings, the Suita score demonstrated better correlations with baPWV than the Framingham risk score in both sexes (men, Suita score R 2 =0.41 and Framingham risk score R 2 =0.37; women, Suita score R 2 =0.54 and Framingham risk score R 2 =0.33). The ROC curve analysis demonstrated the cutoff values of baPWV for moderate-and high-risk groups estimated using the Suita score, and they are as follows: in men, the baPWV cutoff values were 1,350 cm/s in the 40s, 1,430 cm/s in the 50s, 1,520 cm/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Consequently, integrating assessments of arterial stiffness into routine clinical practice holds promise for enhancing and optimizing CVD risk management 38 . We 39 and others 40 substantiated that baPWV can act as a discriminator for identifying individuals at elevated risk of CVD. In the present study, we identified the steady and consistent age-related increases in hbPWV from the early life stage, implying the potential of a more sensitive marker for early detection of CVD risk.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, integrating assessments of arterial stiffness into routine clinical practice holds promise for enhancing and optimizing CVD risk management 38 . We 39 and others 40 substantiated that baPWV can act as a discriminator for identifying individuals at elevated risk of CVD. In the present study, we identified the steady and consistent age-related increases in hbPWV from the early life stage, implying the potential of a more sensitive marker for early detection of CVD risk.…”
Section: Discussionmentioning
confidence: 72%
“…The Suita score, which includes a composite of risk factors, has been used to assess the risk of future cardiovascular disease in the Japanese population 2) . The Suita score is an assessment tool used to predict the 10-year risk of developing cardiovascular heart disease (CHD) 3) ; the cutoff values of brachial-ankle vascular index (baPWV) are shown separately for age and gender using the Suita score 4) . However, in 2022, a new score predicting a 10-year risk of atherosclerotic cardiovascular diseases in Japanese adults was reported in the Hisayama study 5) .…”
Section: See Article Vol 31: 000-000mentioning
confidence: 99%
“…Until now, however, no study has addressed the relationship between brachialankle PWV and the Suita score in the Japanese general population. In this issue of the Journal of Atherosclerosis and Thrombosis, Mori et al examined for the first time the association between brachialankle PWV and the Suita score in a total of 25,602 participants who underwent annual health checkups (57% men) and compared the impact of brachialankle PWV using the FRS and Suita score 8) . Importantly, they tried to obtain the cutoff value of brachial-ankle PWV for CHD risk stratified by sex and age, which is important to apply in daily clinical pract ice.…”
Section: See Article Vol 29: 000-000mentioning
confidence: 99%